Perception of the Grade XII Students Regarding the English Language Curriculum - Panday, Nikesh; Kafle, Ishwori Prasad (Ganeshman Darpan, 2025)
This study explores the perceptions of Grade XII students in Nepal regarding their English language curriculum, focusing on its relevance, effectiveness, and alignment with their academic and professional goals. It evaluates the effectiveness of the curriculum to prepare students for practical communication, enhance their language skills, and respond to contemporary global communication trends. A structured survey questionnaire was employed to collect data from 59 students at a public secondary school in the Kathmandu Valley. The findings indicate that most students view the curriculum positively, particularly its effectiveness in improving language skills (86.5%) and preparing them for future academic and career opportunities (79.6%). 96.6% of students express a strong appreciation for the strength of the curriculum to foster critical thinking and engage themselves with interesting content (88.1%). There is a notable demand for modern language use and relevant subjects, as 96.6% of students emphasize the need for content that align with current communication trends. However, despite the curriculum’s promotion of cultural awareness, 28.8% of students remain neutral, indicating potential areas for enhancement. This study highlights the critical need for ongoing revisions to the curriculum, incorporating student feedback and contemporary language practices to ensure its continued relevance and effectiveness.